College Students and Online Political Expression During the 2016 Election. (August 2018) - Moffett, Kenneth W.; Rice, Laurie L.
While college students traditionally exhibit low levels of political participation and interest in politics, they are more likely to engage in some forms of political expression than their elders. Their greater familiarity with online forms of political expression and engagement potentially lowers their barriers for political involvement. In turn, this potentially draws more young adults into the political process. The authors compare the precursors of expressive forms of online political engagement to those of talking to someone off-line and trying to persuade them to vote for or against a candidate or party among college students. They find that both activities are positively connected with politically oriented activity on social media as well as the frequency with which one reads blogs. They also discover that the mechanisms that explain online political expression are both similar to and different from those that explain off-line attempts at persuasion in several key ways.